2006
DOI: 10.1038/ncb1516
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between PML and SATB1 regulates chromatin-loop architecture and transcription of the MHC class I locus

Abstract: The function of the subnuclear structure the promyelocytic leukaemia (PML) body is unclear largely because of the functional heterogeneity of its constituents. Here, we provide the evidence for a direct link between PML, higher-order chromatin organization and gene regulation. We show that PML physically and functionally interacts with the matrix attachment region (MAR)-binding protein, special AT-rich sequence binding protein 1 (SATB1) to organize the major histocompatibility complex (MHC) class I locus into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(86 citation statements)
references
References 44 publications
8
78
0
Order By: Relevance
“…Next, we used a matrix association assay (30) to experimentally identify regions of the rDNA repeat that are matrix attached. Figure 2A summarizes the procedures used to study the association of rDNA sequences with the nucleolar matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we used a matrix association assay (30) to experimentally identify regions of the rDNA repeat that are matrix attached. Figure 2A summarizes the procedures used to study the association of rDNA sequences with the nucleolar matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to the 3C assay, the MAR-loop assay has been used to detect DNA sequences that are held in close proximity to each other as a result of interaction with the nuclear matrix (30). Unlike the 3C assay, it is not necessary to use formaldehyde cross-linking to maintain integrity of the samples in the MAR-loop assay.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, SATB1 has attracted considerable attention due to its capability to coordinate regulation for many genes which are significantly associated with the growth, invasion and metastasis of a variety of malignancies [14], [15], indicating this “genome organizer” may have a crucial role in the complex gene expression patterns of human cancers by many mechanisms [26], [28]. A recent study by Tu et al .…”
Section: Discussionmentioning
confidence: 99%
“…While initial studies provided controversial results on the role of PML in regulation of MHC-I expression (65)(66)(67)(68), more-recent data convincingly demonstrated that PML acts as a positive regulator of IFN-␄-induced MHC-II expression. Attempts to elucidate the mechanistic basis of this activity revealed that PML induces activation and DNA binding of STAT1 immediately after IFN induction, thereby enhancing transcription of genes such as the MHC-II transactivator (CIITA) (44,45).…”
Section: Discussionmentioning
confidence: 99%